Analisis Pengaruh Pengumuman Kenaikan Harga Bahan Bakar Minyak Terhadap Reaksi Pasar Modal Pada Harga Saham Perusahaan Sub-Sektor Transportasi Tahun 2022 - Margin Hidayat; Ardiansyah Japlani; Deny Edy Widodo (Jurnal Manajemen DIVERSIFIKASI, 2025)
The increasing demand for a stock, the greater the effect on the trading volume of the stock, so that price fluctuations can occur which can increase stock prices and also the stock returns obtained. This study aims to determine whether there is an influence of abnormal returns before and after announcement of the increase in the price of fuel oil (BBM) in Indonesia on the reaction of the Indonesian capital market in the transportation sub-sector and to find out whether there is an effect of trading volume activity before and after the announcement of the increase in the price of fuel oil (BBM) in Indonesia on the reaction of the Indonesian capital market in the sub-sector transportation. The research method used is quantitative. The data taken is secondary data with the company as a sample of the transportation sub-sector company. Data analysis using Paired sample T-test. The results of the study show that 1. There is no significant abnormal return and no effect before and after the announcement of the fuel increase on the reaction of the Indonesian capital market in the transportation sub-sector. 2. There was significant trading volume activity on the days surrounding the announcement. There was no effect of trading volume activity before and after the announcement of the increase in fuel prices on the reaction of the Indonesian capital market on sub-transportation.